Success Stories Developed, Indigenous Technologies Identified and Innovative Methodology Adopted by KVK Pulwama - F.A. Misgar1, Afshan Gul, Tabasum Ara, Amit Kumar (Indian Journal of Extension Education, 2022)
Success story is the essence of any institution ingeneral and KVK's in particular. It depicts the magnitudeof work culture. It is a corner stone on which the edificeof income generating activities followed up with fieldlevel demonstrations, transfer of technology skills,conducting of on farm testing / trials and other relatedactivities of a KVK is built. In fact a KVK withoutsuccess stories is like a human being drained off blood.Success stories act as a catalyst in making an institutionmore vibrant, work oriented and people friendly. Theyinfuse a new life in the work culture of KVK's and makethem more responsive to the needs of the people. Successstories are a gauge for measuring the amount of successa KVK has achieved in the implementation of its workprogramme.